Prenatal expectations and other psycho‐social factors as risk factors of postnatal bonding disturbance. Issue 5 (10th September 2021) - Rusanen, Erja; Vierikko, Elina; Kojo, Tiina; Lahikainen, Anja Riitta; Pölkki, Pirjo; Paavonen, E. Juulia
Abstract: The mother's bond to her baby starts to develop during pregnancy, and it is related to the baby's attachment. We study how the mother's prenatal expectations of her unborn baby, the mother's adult relationships, and postnatal psycho‐social factors (stress, depression, and anxiety) are related to the risk of bonding disturbance. The study comprised 1398 mothers and their unborn babies assessed both during pregnancy and when the babies were 3 months old (47.7% girls). The mother's risk of bonding disturbance was investigated using Brockington's Postpartum Bonding Questionnaire. According to the results, 71 (5.1%) of all the mothers in the study had a risk of a bonding disturbance. In a final adjusted logistic regression model, the most important risk factors were the mother's inability to form positive expectations about relationships with the baby during the third trimester of pregnancy ( AOR  = 7.78, p ≤ .001), maternal postnatal stress ( AOR  = 4.95, p ≤ .001) and maternal postnatal depression ( AOR  = 3.46, p ≤ .01). The results challenge healthcare professionals to screen pregnant mothers to identify at‐risk groups for post‐partum bonding disturbances. Intervention programs to prevent the development of bonding disturbances, and thus their possible serious consequences for children's development, should be considered. Resumen: La unión afectiva entre la madre y su bebé comienza a desarrollarse durante el embarazo y está relacionado a la afectividad del bebé. Estudiamos cómo las expectativas prenatales que la madre tenía de su bebé aún no nacido, las relaciones adultas de la madre, así como los factores sicosociales (estrés, depresión y ansiedad) están relacionados con la alteración de la unión afectiva. El estudio incluyó a 1, 398 madres y sus no nacidos bebés evaluados ambos durante el embarazo y cuando los bebés tenían tres meses de nacidos (47.7% niñas). El riesgo de la madre de alteraciones en la unión afectiva fue investigado usando el Cuestionario Brockington sobre la Unión Afectiva Posterior al Parto. De acuerdo con los resultados, 71 (5.1%) de todas las madres en el estudio presentaban un riesgo de alteración de la unión afectiva. En un modelo final de regresión logístico ajustado, los más importantes factores de riesgo fueron la inhabilidad de la madre de formar expectativas positivas acerca de las relaciones con el bebé durante el tercer trimestre del embarazo (AOR = 7.78, p < .001), el estrés materno postnatal (AOR = 4.95, p < .001) y la depresión materna postnatal (AOR = 3.46, p < .01). Los resultados presentan un reto a los profesionales del cuidado de la salud para examinar a mujeres embarazadas con el fin de identificar grupos bajo riesgo de alteraciones en la unión afectiva posterior al parto. Se deben considerar programas de intervención para prevenir el desarrollo de alteraciones en la unión afectiva y, por tanto, posibles serias consecuencias para el desarrollo de los niños. Résumé: Le lien de la mère avec son bébé commence à se développer durant la grossesse, et est lié à l'attachement du bébé. Nous étudions la manière dont les attentes prénatales que la mère se fait de son bébé à naître, les relations adultes de la mère, et les facteurs postnatals psycho‐sociaux (stress, dépression, anxiété) sont liés au risque de trouble du lien. L'étude a compris 1398 mères et leurs bébé à naître évalués à la fois durant la grossesse et quand les bébés avaient trois mois (47, 7% de filles). Le risque de trouble du lien de la mère a fait l'objet de l'étude, au moyen du Questionnaire du Lien Postpartum de Brockington. Selon les résultats, 71 (soit 5, 1%) de toutes les mères de l'étude avaient un risque de trouble du lien. Dans un modèle de régression logistique ajusté final les facteurs de risque les plus importants étaient l'incapacité de la mère à former des attentes positives sur les relations avec le bébé durant le troisième trimestre de la grossesse (AOR – 7, 78, p ≤, 001), le stress postnatal maternel (AOR = 4, 95, p ≤, 001) et la dépression postnatale maternelle (AOR = 3, 46, p ≤, 01). Les résultats défient les professionnels de la santé de dépister les mères enceintes afin d'identifier les groupes à risque de troubles du lien postpartum. Des programmes d'intervention destinés à prévenir le développement de troubles du lien ainsi que leurs conséquences sévères pour le développement des enfants devraient être considérés. Zusammenfassung: Pränatale Erwartungen und andere psychosoziale Faktoren als Risikofaktoren für postnatale Bindungsstörungen Die Beziehung der Mutter zu ihrem Baby entwickelt sich bereits während der Schwangerschaft und steht im Zusammenhang mit der Bindung des Babys. Wir untersuchen, wie die pränatalen Erwartungen der Mutter an ihr ungeborenes Kind, die Beziehungen der Mutter zu Erwachsenen und postnatale psychosoziale Faktoren (Stress, Depression und Angst) mit dem Risiko einer Bindungsstörung zusammenhängen. Die Studie umfasste 1.398 Mütter und ihre ungeborenen Babys (47, 7 % Mädchen), die sowohl während der Schwangerschaft als auch im Alter von drei Monaten untersucht wurden. Das Risiko der Mütter für eine Bindungsstörung wurde mit Hilfe des Brockington‐Fragebogens zur postpartalen Bindung untersucht. Die Ergebnisse zeigen, dass 71 (5, 1 %) der Mütter in der Studie ein Risiko für eine Bindungsstörung hatten. In einem endgültigen bereinigten logistischen Regressionsmodell waren die wichtigsten Risikofaktoren die Unfähigkeit der Mutter, während des dritten Trimesters der Schwangerschaft positive Erwartungen an die Beziehung zum Baby zu entwickeln (AOR = 7, 78, p ≤ .001), mütterlicher postnataler Stress (AOR = 4, 95, p ≤ .001) und mütterliche postnatale Depression (AOR = 3, 46, p ≤ .01). Die Ergebnisse zeigen auf, wie wichtig es ist, schwangere Mütter zu untersuchen, um Risikogruppen für postpartale Bindungsstörungen zu identifizieren. Interventionsprogramme zur Vorbeugung von Bindungsstörungen und deren möglichen schwerwiegenden Folgen für die Entwicklung der Kinder sollten in Betracht gezogen werden. 抄録: 出生後のボンディング (情緒的絆の) 障害のリスク因子としての出生前の期待やその他の心理社会的要因 母親のおなかの子への絆は妊娠中に芽生え始め、そして、そのことは生れくる赤ちゃんのアタッチメントに関係する。おなかの中の赤ちゃんへの母親の出生前の期待、母親の対人関係、そして出生後の心理社会的要因 (ストレス、抑うつ、不安) が、ボンディング障害のリスクとどのように関連しているかを研究する。この研究は、1, 398人の母親とおなかの子 (女児47.7％) を対象とし、妊娠中と生後3か月の2回に評価を行った。母親のボンディング障害のリスクは、ブロッキントン産後ボンディング質問票を使用して調査した。 結果によると、研究に参加したすべての母親のうち71人 (5.1％) にボンディング障害のリスクを認めた。最終調整後のロジスティック回帰モデルでは、最も重要なリスク因子は、母親が妊娠後期に赤ちゃんとの関係性に前向きな期待を形成できないこと (AOR = 7.78、p≤.001) 、母親の産後ストレス (AOR = 4.95、p≤.001) および、母親の産後うつ病 (AOR = 3.46、p≤.01) であった。この結果は、健康保健専門家の課題として、妊娠中の母親をスクリーニングし、産後のボンディング障害のリスク群を特定することを求めている。ボンディング障害が進行し、例えば子どもの発達に起こりえる深刻で重要な結果を予防する介入プログラムが課題である。 摘要: 母亲与婴儿的关系在怀孕期间就开始发展, 这与婴儿的依恋有关。我们研究了母亲对未出生婴儿的产前期望、母亲的成人关系以及产后心理社会因素 (压力、抑郁和焦虑) 与亲子关系障碍的风险之间的关系。这项研究包含了1, 398名母亲及其未出生的婴儿, 并对他们在怀孕期间和婴儿三个月大 (47.7% 是女孩) 时进行了评估。采用Brockington的"产后连结问卷"调查了母亲发生亲子关系障碍的风险。根据研究结果, 在所有参与研究的母亲中, 有71人 (5.1%) 存在发生亲子关系障碍的风险。在最终调整后的逻辑回归模型中, 最重要的危险因素是母亲在妊娠晚期不能对与婴儿的关系形成积极的期望 (AOR = 7.78, p ≤ .001), 进而造成母亲产后压力 (AOR = 4.95, p ≤ .001) 和产后抑郁 (AOR = 3.46, p ≤ .01) 。研究结果提议医护人员对孕妇进行筛查, 以确定产后亲子关系障碍的高危人群。应考虑采取干预计划, 以防止亲子关系障碍的发展, 以及其对儿童发展可能产生的严重后果。 ملخص: توقعات ما قبل الولادة وغيرها من العوامل النفسية والاجتماعية كعوامل خطر لاضطراب الترابط بعد الولادة يبدأ ارتباط الأم بطفلها في التطور أثناء الحمل ، ويرتبط ذلك بتعلق الطفل. نتناول في هذه الدراسة كيف ترتبط توقعات الأم قبل الولادة لطفلها ، وعلاقات الأم البالغة، والعوامل النفسية والاجتماعية بعد الولادة (الإجهاد والاكتئاب والقلق) بخطر اضطراب الترابط. شملت الدراسة 398 1 أما وأطفالهن الذين لم يولدوا بعد. وتم تقييمهم أثناء الحمل وعندما كان عمر الأطفال ثلاثة أشهر (47.7 من الإناث). تم التحقيق في خطر اضطراب الترابط عند الأمهات باستخدام استبيان بروكينغتون الخاص بالترابط بعد الولادة. ووفقا للنتائج، فإن 71 (5.1 في المائة) من بين جميع الأمهات في الدراسة كان لديهن خطر اضطراب الترابط. ومن خلال نموذج انحدار لوجستي معدل ، كانت أهم عوامل الخطر هي عدم قدرة الأم على تكوين توقعات إيجابية حول العلاقات مع الطفل خلال الثلث الثالث من الحمل (78AOR = 7.، p ≤.001)، إجهاد الأمومة بعد الولادة (AOR = 4.95، p ≤.001) واكتئاب ما بعد الولادة الأمومي (AOR = 3.46، p ≤.01). تتحدى النتائج أخصائيي الرعاية الصحية لفحص الأمهات الحوامل لتحديد الفئات المعرضة لخطر اضطرابات الترابط بعد الولادة. وينبغي النظر في برامج التدخل لمنع حدوث اضطرابات الترابط، وبالتالي تفادي عواقبها الخطيرة المحتملة على نمو الأطفال.